Practical handbook of photovoltaics : fundamentals and applications - McEvoy, A. J.; Markvart, T.; Castañer, Luis (Academic Press, 2012)
As part of the growing sustainable and renewable energy movement, the design, manufacture and use of photovoltaic devices is increasing in pace and frequency. The Handbook of Photovoltaics will be a 'benchmark' publication for those involved in the design, manufacture and use of these devices. The Handbook covers the principles of solar cell function, the raw materials, photovoltaic systems, standards, calibration, testing, economics and case studies. The editors have assembled a cast of internationally-respected contributors from industry and academia. The report is essential reading for: Physicists, electronic engineers, designers of systems, installers, architects, policy-makers relating to photovoltaics. * A thorough update to the 'benchmark' publication from a cast of industrial and academic international experts ensures top quality information from multiple stakeholder perspectives *Covers all things PV- from principles of solar cells and their raw materials, to the installation and design of full PV systems, including standards, testing, economics and environmental impacts * Case studies, practical examples and reports on the latest advances take the new edition of this amazing resource beyond a vast collection of knowledge, into the realm of real world applications.